1993
DOI: 10.1083/jcb.120.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the translational mobility of a small solute in cell cytoplasm.

Abstract: Abstract. The purposes of this study were: (a) to measure the translational mobility of a small solute in cell cytoplasm; (b) to define quantitatively the factors that determine solute translation; and (c) to compare and contrast solute rotation and translation. A small fluorescent probe, 2,7-bis-(2-carboxyethyl)-5-(and 6-)-carboxyfluorescein (BCECF), was introduced into the cytoplasm of Swiss 3T3 fibroblasts. BCECF translation was measured by fluorescence recovery after photobleaching; rotation was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
243
4
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(270 citation statements)
references
References 41 publications
(41 reference statements)
21
243
4
2
Order By: Relevance
“…Although these simulation results are coherent and in agreement with 2D simulations [36][37][38][39][40][41][44][45][46][47] , there are experimental 3D studies 31,35 that show a reverse result for the limiting diffusion coefficient and the anomalous diffusion exponent values.…”
Section: I) Effect Of Obstacle Density and Sizesupporting
confidence: 80%
See 1 more Smart Citation
“…Although these simulation results are coherent and in agreement with 2D simulations [36][37][38][39][40][41][44][45][46][47] , there are experimental 3D studies 31,35 that show a reverse result for the limiting diffusion coefficient and the anomalous diffusion exponent values.…”
Section: I) Effect Of Obstacle Density and Sizesupporting
confidence: 80%
“…There is a region with a linear decreasing of log(<r 2 >/t), which corresponds to an anomalous diffusion behaviour, followed by a region with a smaller constant diffusion coefficient (D*) characteristic of normal diffusion. It should be noticed that, as it was reported in other studies 17,[36][37][38][39][40][41] , the initial region of normal diffusion (when the diffusing particles are not still affected by the crowding obstacles) is not observed in the present onlattice simulations. The plot starts at a position, D 0 '(f), lower than D 0 (f) (the initial normal diffusion coefficient given by eqn (7) not observed in the simulation), which value depends on the discretization of the lattice, the obstacle size and the excluded volume, and immediately decreases to reach the linear anomalous diffusion region.…”
Section: C Characteristic Parameters Of the Diffusion Processsupporting
confidence: 57%
“…These mobilities are directly proportional to the respective diffusion coefficients and, therefore, should be inversely proportional to cytoplasmic viscosity (21). If viscosity is a major factor in determining the SPQ fluorescence response, the quenching constants will be higher, since a potential decrease in cytoplasmic viscosity can be expected during swollen conditions (19). This suggests a decrease in SPQ fluorescence response on cell swelling, but all the experimental observations 3 in this study and others (15,30) show an increase in SPQ fluorescence with a decrease in extracellular osmolarity.…”
Section: Significance Of Intracellular Viscositymentioning
confidence: 99%
“…It was initially thought that the viscosity had to depend on the molecular size to account for the sieving effect due to the cytoskeletal network and other macromolecular structures. For this reason, solutes diffusion was described by the translational diffusion coefficient [28], depending on the viscosity of the fluid-phase cytoplasm and on the collisions with intracellular components. The former, representing the viscosity sensed by a small solute in the absence of interactions with macromolecules and organelles, is 1.2-1.4 times that of water [20].…”
Section: Diffusion the Molecular Species Diffusion Is Expressed In Tmentioning
confidence: 99%
“…The net viscosity of the cytoplasm of Swiss 3T3 fibroblasts with respect to small solutes such as metabolites and nucleic acids was measured by Kao et al [28] using fluorescence recovery after spot-photobleaching (FRAP) [4]. They found that mobility was around four to fivefold slower than in water.…”
Section: Diffusion the Molecular Species Diffusion Is Expressed In Tmentioning
confidence: 99%